2013
DOI: 10.1371/journal.pone.0064138
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of Clinical-Grade CD19-Specific T Cells Stably Expressing Chimeric Antigen Receptor Using Sleeping Beauty System and Artificial Antigen Presenting Cells

Abstract: Adoptive transfer of T cells expressing a CD19-specific chimeric antigen receptor (CAR) is being evaluated in multiple clinical trials. Our current approach to adoptive immunotherapy is based on a second generation CAR (designated CD19RCD28) that signals through a CD28 and CD3-ζ endodomain. T cells are electroporated with DNA plasmids from the Sleeping Beauty (SB) transposon/transposase system to express this CAR. Stable integrants of genetically modified T cells can then be retrieved when co-cultured with des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
150
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 27 publications
1
150
0
Order By: Relevance
“…The SB100X transposase meditates the stable genomic integration of the expression cassette into the host cell’s genome, which allows for long-term transgene expression. Effective SB -mediated gene transfer has been reported for various in vitro and in vivo disease models,41, 42, 43 and it has been approved for clinical application of genetically modified T cells to treat B-lymphoid malignancies 44, 45. We have reported long-term and continuous PEDF secretion by RPE cells that were transfected with the PEDF transgene using the SB100X transposon system 25 and demonstrated that the subretinal transplantation of PEDF-transfected cells in a rat model of CNV reduces neovascularization and inhibits new vessel formation 46 …”
Section: Discussionmentioning
confidence: 99%
“…The SB100X transposase meditates the stable genomic integration of the expression cassette into the host cell’s genome, which allows for long-term transgene expression. Effective SB -mediated gene transfer has been reported for various in vitro and in vivo disease models,41, 42, 43 and it has been approved for clinical application of genetically modified T cells to treat B-lymphoid malignancies 44, 45. We have reported long-term and continuous PEDF secretion by RPE cells that were transfected with the PEDF transgene using the SB100X transposon system 25 and demonstrated that the subretinal transplantation of PEDF-transfected cells in a rat model of CNV reduces neovascularization and inhibits new vessel formation 46 …”
Section: Discussionmentioning
confidence: 99%
“…A construct to select for inducible caspase 9 (iC9) FLAG-DHFR and 3Ј to the IL-12p40 stop site ligated the three components into the TS SS G backbone in a four-part ligation. All constructs described integrate into the cellular genome with the aid of Sleeping Beauty transposase (20).…”
Section: Methodsmentioning
confidence: 99%
“…We genetically modified primary circulating T cells using our SB transposon/transposase system that we adapted for human gene transfer. Indeed, we have achieved institutional and federal regulatory approvals for four clinical trials (NCT00968760, NCT01497184, NCT01362452, NCT01653717) infusing autologous and allogeneic T cells genetically modified with an SB encoding a CD19-specific CAR and propagation on aAPC (clone #4) (21,22,37). To generate clinically relevant numbers of D-CAR + T cells for adoptive transfer, T cells were expanded numerically on "designer" aAPC.…”
Section: Discussionmentioning
confidence: 99%
“…35050-061; Life Technologies) and 10% heat-inactivated FBS (HyClone). D-CAR + T cells were generated as previously described for CD19-specific CAR + T cells (37). In brief, T cells were electroporated with DNA plasmids from the SB system coding for D-CAR and SB11 and were propagated on aAPCs (clone #4) preloaded with Dectin-1-specific mAb in the presence of IL-2 and IL-21.…”
Section: Methodsmentioning
confidence: 99%